Distribution and spatio-temporal biomass trends of red mullets across the Mediterranean - Tserpes, George; Massutí, Enric; Fiorentino, Fabio; Facchini, Maria Teresa; Viva, Claudio; Jadaud, Angélique; Joksimovic, Aleksandar; Pesci, Paola; Piccinetti, Corrado; Sion, Letizia; Thasitis, Ioannis; Vrgoc, Nedo (Scientia Marina, 2019)
The present work examines the spatio-temporal biomass trends of Mullus barbatus and Mullus surmuletus in the Mediterranean Sea through the analysis of a time series of data coming from the Mediterranean International Trawl Surveys (MEDITS), accomplished annually from 1994 to 2015. The biomass of both species showed clear declining trends below 150 to 200 m depth, which were steeper in the case of M. barbatus. Increases in temporal biomass trends were observed for M. barbatus from 2008 onward in most geographic sub-areas (GSAs), while stability was mostly observed for M. surmuletus. For both species, dynamic factor analysis revealed similarities among neighbouring GSAs and the subsequent cluster analysis identified two major GSA groups corresponding to the eastern and western basins of the Mediterranean. Overall, the results suggested that the combined effects of fishing and environmental conditions determine species abundance variations, but the relative importance of each component may vary among areas.